Red list of vascular flora of Wielkopolska (Poland) - Jackowiak, Bogdan; Celka, Zbigniew; Chmiel, Julian; Latowski, Karol; Żukowski, Waldemar (Biodiversity: Research and Conservation, 2007)
The article presents the second, substantially changed edition of the red list of vascular plants of Wielkopolska. The region under study covers the area of 50 000 km2 and constitutes a significant part of the Central European Lowlands. The east and central part of Wielkopolska includes an important historical territory which, from the 8th-10th century, was the center of Polish statehood creation. The flora of this region has been the subject of systematic investigations since the first half of the 19th century. Thanks to that, it is possible to evaluate the longterm changes resulting from human activities. Currently, the red list consists of 601 taxons, which accounts for 30% of the vascular flora of Wielkopolska. Apart from the dominant native plants, the list includes also archaeophytes (42 species). In comparison to the first edition of the list, further increase in the flora endangerment has been observed. At present, 52 species should be considered extinct. Moreover, the number of taxons critically endangered (87 species) has also significantly increased. A detailed analysis of the data presented in the publication emphasizes taxonomical, chorological and ecological aspects of species extinction. The separate part of the red list has been dedicated to the 13 species which conservation requires designation of Special Areas of Conservation (SACs) within the Natura 2000 network.